Selection and assortment of the variables describing the relationship between the economy and the general government sector size by application of the LEM2 algorithm - Tomasz Skica; Jacek Rodzinka; Barbara Fryc (e-Finanse: Financial Internet Quarterly, 2016)
This paper reverses the relatively frequent examined interrelation that links an impact of the public sector (and within it the general government sector) on the economy of the analyzed countries. The article analyses whether the size of the general government sector is a function of the economy expressed through variables that were adopted for research. Realization of the research objective that was raised in this article focused on typing, grouping and selecting variables that describe respectively: the economy and the size of the sector. For identifying relationships between variables assigned to each group, the LEM2 algorithm was used. Rules that were generated by the application of this algorithm provided not only information about the relationships of individual variables, but also provided an indication of how frequently they occurred in relation to the examined pairs of variables describing the economy and the size of the general government sector. The subject of research was EU Member States (their economy and public finance systems) and the research period was set on the years 2000 to 2013 (inclusive) Among the economic variables and variables describing the size of the sector, there were included both standard variables used in the analyzes dedicated to macroeconomic issues as well as variables that the authors' team selected in order to test their applicability in describing the economy and the size of the general government sector. Such a composition of the variables is well-founded as, besides the main objective of this article (i.e. to establish a link between the economic situation and size of the general government sector) the additional effect of research, and that is the optimization of the selected variables that are used to explain the relationship of the economy and the size of the sector.
Keywords: E62; H11; H20; H50; H60; 330; Economy; general government sector; central government; economy; public finance; general government sector size